1949
DOI: 10.3181/00379727-70-16857
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Alternation in Experimental Coronary Artery Occlusion.

Abstract: 155gen content has entered the lipide extract. Cirrhosis affects the lipide content so that it increases above normal but not as high as the normal fasted liver cytoplasm. The phospholipide in the cirrhotic liver decreases, but here also there seems to be a lipide present with a high nitrogen content.The iodine value of both the normal fasted and the cirrhotic-fasted liver cytoplasms decreased below that of normal. These results are in accord with those of WinteP in that he found that after feeding carbon tetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1960
1960
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…In contrast to concordant alternans, discordant alternans is a less studied phenomenon 13,27 in cardiac tissue where its mechanism is unknown. In the present study, we focused on the conditions necessary to produce dis- cordant alternans in spatially uniform tissue.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to concordant alternans, discordant alternans is a less studied phenomenon 13,27 in cardiac tissue where its mechanism is unknown. In the present study, we focused on the conditions necessary to produce dis- cordant alternans in spatially uniform tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover it has been suggested that intracellular calcium increases during acute ischaemia, and that this is related to arrhythmia generation (Clusin, Buchbinder & Harrison, 1983). Mechanical alternans has been reported coupled with electrical alternans, and there is evidence for a link between 'odd type' alternans and both calcium entry and calcium cycling (Hellerstein & Liebow, 1950;Hirata et al 1980;Wohlfahrt, 1982;Hashimoto et al 1983;Bateman et al 1987). During steady electromechanical alternans the high force can be associated with the short action potential.…”
Section: Possible Mechanisms Of Ischaemic Alternansmentioning
confidence: 99%
“…J. LAB monophasic action potentials (Lab & Woollard, 1978) and the electrocardiogram (Hellerstein & Liebow, 1950;Hashimoto, Suzuki, Miyake & Nakashima, 1983;Carson et al 1986) has been noted to occur during ischaemia in the intact preparation.…”
Section: Electrical Restitution Curvesmentioning
confidence: 99%
“…Development of the giant R wave in stationary epicardial "mat" electrodes positioned across the ischemic zone . The unipolar electrocardiograms were recorded simultaneously from 14 epicardial electrodes (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) with an inter-electrode distance of 1mm and also from a reference unipolar intra-left ventricular electrode (Ref.…”
Section: Baselinementioning
confidence: 99%